2021
DOI: 10.3390/nano11051101
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Non-Volatile InGaZnO Based Flash Memory Device Embedded with a Monolayer Au Nanoparticles

Abstract: Non-volatile memory (NVM) devices based on three-terminal thin-film transistors (TFTs) have gained extensive interest in memory applications due to their high retained characteristics, good scalability, and high charge storage capacity. Herein, we report a low-temperature (<100 °C) processed top-gate TFT-type NVM device using indium gallium zinc oxide (IGZO) semiconductor with monolayer gold nanoparticles (AuNPs) as a floating gate layer to obtain reliable memory operations. The proposed NVM device exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The FG-type IGZO TFT for memory generally utilized metal nanoparticles as a FG. , The electronic synaptic transistor that uses IGZO and metal nanoparticles was proposed by Kim et al This study showed high-performance synaptic functions in an MNIST simulation. Unlike conventional FG-type TFT, this structure was impressive in that the metal nanoparticles were inserted between the dielectric and IGZO.…”
Section: Igzo-based Electronic- And/or Photonic-synaptic Devicesmentioning
confidence: 99%
“…The FG-type IGZO TFT for memory generally utilized metal nanoparticles as a FG. , The electronic synaptic transistor that uses IGZO and metal nanoparticles was proposed by Kim et al This study showed high-performance synaptic functions in an MNIST simulation. Unlike conventional FG-type TFT, this structure was impressive in that the metal nanoparticles were inserted between the dielectric and IGZO.…”
Section: Igzo-based Electronic- And/or Photonic-synaptic Devicesmentioning
confidence: 99%
“…The floating layer is anticipated to be the other important constituent in non-volatile memory devices because it determines the charge storage capacity and endurance/retention operation. For traditional non-volatile memory devices other than polycrystalline Si [1], high-k dielectric materials such as HfO 2 [17][18][19], TaN [20], organic films [21,22], and metallic metal (Au, Pt) nanoparticles or nanoclusters [23][24][25] have also been used as floating layers to store and erase charge. Among them, metallic nanocrystal floating layers have several advantages because of their high trapping states, stable retention, and larger memory windows [26].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Metallic nanocrystals (e.g., Au) with a high density of states are favored. [1,2] High-k insulating layer, typically, HfO x , is also used because of its excellent charge-trapping ability, reduced coupling crosstalk and good scalability. [3][4][5] However, with thickness scaling down to 10 nm or lower, large leakage becomes and long-term operability of the optoelectronic FGNVM.…”
Section: Introductionmentioning
confidence: 99%